Education, Mirror Therapy, and Foot Massage to Improve the Quality of Life of Stroke Patients (Motor Status Parameters) - Anggi Pratiwi; Zahri Darni; Denny Prasetyanto (Jurnal Ners, 2026)
Background:Education, mirror therapy, and foot massage have been considered alternative treatments to improve muscle strength in post-stroke patients. However, little is known about the combination of these three methods. Objective: To identify the effectiveness of the combination of education, mirror therapy, and foot massage on changes in muscle strength in post-stroke patients. Methods: This study used a quasi-experimental design with pre-test and post-test control groups. Fifty-four samples were selected using purposive sampling, of which 27 were randomly assigned to the experimental and control groups. Muscle strength was measured using a muscle strength scale. Data analysis was performed using paired t- tests and independent t-tests. Results: In the treatment group, there was an increase in average muscle strength from 2.0 to 3.8. Statistical tests showed a significant difference (p = 0.001). In the control group, average muscle strength increased from 2.1 to 2.6, but the statistical test results were not significant (p = 0.085). The test for differences between groups after intervention also showed a significant difference (p < 0.05), so it can be concluded that the intervention had a significant effect on increasing muscle strength in stroke patients compared to the control group. Conclusion : Education, mirror therapy and foot massage are effective in increasing muscle strength in post-stroke patients.